PENERAPAAN MEDIA FILM DALAM PEMBELAJARAN FIQIH KELAS V MADRASAH IBTIDAIYAH SWASTA (MIS) GUPPI CININI INDRAMAYU - Khoirul Umam; Moch. Hasyim Fanirin (JOEL: Journal of Educational and Language Research, 2023)
This research was conducted because of a lack of enthusiasm, interest, and lack of focus of students so that learning becomes monotonous due to the fact that many students don't focus on learning and need a new innovation in conveying material as well as any obstacles that arise when using the movie as a media. This study aims to determine the application and the obstacles faced and the solution to the application of the movie as media in fiqh learning for grade 5 students of Madrasah Ibtidaiyah GUPPI Cinini Indramayu. This research was conducted by using a qualitative research and descriptive approach. The data collection techniques were carried out in 4 ways, they are: 1) observations, 2) interviews, 3) tests, and 4) documentation. The object of this research is movie as learning media and students using Fiqh subjects. Based on the results of the application of the movie as media in fiqh learning at Madrasah Ibtidaiyah GUPPI Cinini, it went well from screening the movie to answering questions. The obstacles faced in the application of the movie as media in fiqh learning for grade 5 students of Madrasah Ibtidaiyah GUPPI Cinini were the limitations of school facilities such as LCD projectors and computers or laptops plus a socket that was too far away. So the solution is to bring your own LCD projector and laptop and use a long cable to support a socket that is too far away.